2013
DOI: 10.4161/rdis.24995
|View full text |Cite
|
Sign up to set email alerts
|

Drosophilaas a starting point for developing therapeutics for the rare disease Duchenne Muscular Dystrophy

Abstract: Progress into developing therapeutics for rare diseases can be accelerated for those diseases that can be modeled in genetically tractable organisms. Here we comment on one disease, Duchenne Muscular Dystrophy (DMD), modeled in Drosophila that brought together disparate lines of research toward the goal of developing a therapeutic. Though the bioactive lipid sphingosine 1-phosphate (S1P) has been implicated in many anabolic processes in many cell types and tissues, including muscle, this work confirmed the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Informative Drosophila models have been generated for several neuromuscular diseases and for six of the nine classes of muscular dystrophy including Duchenne [ 58 , 61 ], myotonic [ 57 , 102 ], congenital, including certain dystroglycanopathies [ 58 , 59 , 103 , 104 ], Emery-Dreyfus [ 60 , 105 ], oculopharyngeal [ 56 ], and limb-girdle [ 54 ]; however, no Drosophila model for FSHD based on any candidate gene has been reported. Therefore, the Drosophila lines presented here that will allow investigations into the functions of two genes important to FSHD and will fill an important void in FSHD research by providing valuable resources for those studying muscle development and FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…Informative Drosophila models have been generated for several neuromuscular diseases and for six of the nine classes of muscular dystrophy including Duchenne [ 58 , 61 ], myotonic [ 57 , 102 ], congenital, including certain dystroglycanopathies [ 58 , 59 , 103 , 104 ], Emery-Dreyfus [ 60 , 105 ], oculopharyngeal [ 56 ], and limb-girdle [ 54 ]; however, no Drosophila model for FSHD based on any candidate gene has been reported. Therefore, the Drosophila lines presented here that will allow investigations into the functions of two genes important to FSHD and will fill an important void in FSHD research by providing valuable resources for those studying muscle development and FSHD.…”
Section: Discussionmentioning
confidence: 99%
“…To recapitulate MD, different mutations in Dys were generated in D. melanogaster that show mobility defects, age-dependent muscle degeneration, and neuronal and circulatory defects [ 263 , 264 , 265 ]. This model was also used to screen different phenotype ameliorating compounds [ 266 ].…”
Section: Modeling Dystrophy-associated Cardiomyopathymentioning
confidence: 99%
“…Studies in Drosophila, which does not have identified S1PRs, have shown that genetic increase of the levels of the S1P or delivery of the S1P lyase inhibitor THI suppresses dystrophic muscle degeneration [190]. In mice S1P can act as a ligand for S1PRs and as a HDAC inhibitor.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%